2008
DOI: 10.1007/s00468-008-0220-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in patterns of cell death between ray parenchyma cells and ray tracheids in the conifers Pinus densiflora and Pinus rigida

Abstract: Differences in patterns of cell death between ray parenchyma cells and ray tracheids in the conifers Pinus densiflora and Pinus rigida were clarified. Differentiation and cell death of ray tracheids occurred successively and both were related to the distance from the cambium. In this respect, they resembled those of longitudinal tracheids. Thus, the cell death of short-lived ray tracheids could be characterized as time-dependent programmed cell death. In contrast, ray parenchyma cells survived for several year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 20 publications
5
45
0
Order By: Relevance
“…In analogy to our previous study on a softwood (Zheng et al 2014a,b) it can be presumed that RPCs of hardwoods are also more lignified in hW than in sW. Nakaba et al (2008Nakaba et al ( , 2012 reported that the number of dead RPCs in sW increased from the cambium side towards the pith in both softwood and hardwood. In the TZ, the number of dead RPCs increased rapidly, and almost all of the RPCs were dead in the hW.…”
Section: Evaluation Of Tof-sims Datasupporting
confidence: 74%
See 1 more Smart Citation
“…In analogy to our previous study on a softwood (Zheng et al 2014a,b) it can be presumed that RPCs of hardwoods are also more lignified in hW than in sW. Nakaba et al (2008Nakaba et al ( , 2012 reported that the number of dead RPCs in sW increased from the cambium side towards the pith in both softwood and hardwood. In the TZ, the number of dead RPCs increased rapidly, and almost all of the RPCs were dead in the hW.…”
Section: Evaluation Of Tof-sims Datasupporting
confidence: 74%
“…Lignification and the structure of the cell wall in different types of RPCs in Populus maximowiczii Henry were compared by Murakami et al (1999) by means of the UV microscopy, POM, and TEM. The pattern of cell death, the process of lignification, and the function of RPCs in several species of both softwood and hardwood species were studied by Nakaba et al (2006Nakaba et al ( , 2008Nakaba et al ( , 2012 by means of microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Some of ray parenchyma cells and axial parenchyma cells contained nuclei and plastids, because these cells survived longer when compared to other cells, such as fiber, tracheary elements, and vessels. (Abe et al 2011;Nakaba et al 2006;Nakaba et al 2008). Xylem was formed after PCD.…”
Section: Plastid Distributionmentioning
confidence: 99%
“…When comparing different studies it is important to understand the influence of the composition of the woody portion of the stem from which the RNA is extracted. This RNA from woody tissues is expected to comprise primarily of RNA from the outermost layer of woody differentiating xylem, since the final autolysis of cellular contents is slow in conifer tracheids (Bollhöner et al 2012) but it will also contain RNA from rays and resin duct parenchyma, as the latter can live for more than 30 years in Pinus (Nakaba et al 2008). The xylem transcriptomes obtained from the 2-year-old saplings used in this study likely reflect developmentally young, but woody, outer xylem seen immediately below the gelatinous 'developing xylem' of older trees.…”
Section: General Observations On the Transcriptomes Induced By Ethephonmentioning
confidence: 99%